2017
DOI: 10.21037/jss.2017.08.09
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of microendoscopy-assisted extreme lateral interbody fusion

Abstract: Background: Extreme lateral interbody fusion (XLIF) has rapidly become a popular operative procedure for lumbar canal stenosis and scoliosis. This approach provides direct access to the lateral aspect of the disc with minimal disruption of spinal structures, including ligaments and muscles. However, it involves risk of injuries to the lumbar nerve plexus, segmental artery and intestinal tract because of the limited surgical field.This study aimed to clarify the benefit of using a microendoscope to prevent thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…To address these complications, we have previously reported the advantages of microendoscopy-assisted XLIF over conventional XLIF [19]. In addition, the use of microendoscopy has been implemented to assist operative procedures since the introduction of OLIF at our hospital.…”
Section: Introductionmentioning
confidence: 99%
“…To address these complications, we have previously reported the advantages of microendoscopy-assisted XLIF over conventional XLIF [19]. In addition, the use of microendoscopy has been implemented to assist operative procedures since the introduction of OLIF at our hospital.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 42 articles were eventually included in our systematic review [1, 35, 79, 11, 1315, 17, 1925, 2730, 32, 33, 3641, 4346, 49, 51, 52, 55, 56, 59, 60]. Two studies were level II evidence [19, 52], seven were level III evidence [11, 24, 32, 46, 49, 56, 59], and the remaining were level IV evidence (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[8] Utilizing micro endoscopy in 96 patients undergoing 1-3 level MI XLIF for lumbar stenosis/ scoliosis, Segawa et al (2017) found no injuries to the segmental arteries. [12] Of the 1995 XLIF studied over 2 years by Fujibayashi et al (2017), the overall complication rate was 18%, and included a 0.03% incidence of major vascular injuries. [7] Amongst Paterakis et al (2018) study involving 12 XLIF, complications included no major vascular injuries.…”
Section: Major Vascular Complications In Small/larger Case Series Of Xlif/mi Xlifmentioning
confidence: 98%
“…The incidence of major vascular injuries occurring for transpsoas XLIF/MI XLIF performed in the 5 small and larger case series involving a total of 6,732 patients (range from 12 to 4,607 patient/series) ranged from 0% (3 studies) to 0.03% (1 study) to 0.4% (1 study) [Table 1]. [7,8,10,12,13] Karikari et al (2011), evaluated 22 MI Thoracic/Thoracolumbar XLIF involving 47 levels; the 3 adverse events did not include any vascular injuries [Table 1]. [8] Utilizing micro endoscopy in 96 patients undergoing 1-3 level MI XLIF for lumbar stenosis/ scoliosis, Segawa et al (2017) found no injuries to the segmental arteries.…”
Section: Major Vascular Complications In Small/larger Case Series Of Xlif/mi Xlifmentioning
confidence: 99%
See 1 more Smart Citation